A subtelomeric DNA sequence is required for correct processing of the macronuclear DNA sequences during macronuclear development in the hypotrichous ciliate Stylonychia lemnae. - Jönsson, F (1999)
During macronuclear differentiation in ciliated protozoa a series of programed DNA reorganization processes occur. These include the elimination of micronuclear-specific DNA sequences, the specific fragmentation of the genome into small gene-sized DNA molecules, the de novo addition of telomeric sequences to these DNA molecules and the specific amplification of the remaining DNA molecules. Recently we constructed a vector containing the modified micronuclear version of macronuclear destined DNA sequences that was correctly fragmented and telomeres were added de novo after injection into the developing macronucleus. It therefore must contain all the cis- acting sequences required for these processes. We made a series of vectors deleting different sequences from the original vector. It could be shown that at least in the case studied here no micronuclear-specific sequences are required for specific fragmentation of the genome and telomere addition. However, a short subtelomeric sequence at the 3[prime]-end is essential for these processes, whereas no specific cut seems to occur at the 5[prime]-end. In addition, we can show that the processing activity is restricted to a short period of time during macronuclear differentiation and that a preceding transcription is required for correct processing of macronuclear-destined DNA sequences. Possible mechanisms of these processes will be discussed.